Pathway-Based Reduction of Repeat Head Computed Tomography for Patients With Complicated Mild Traumatic Brain Injury: Implementation and Outcomes. Issue 4 (19th January 2021) - Stippler, Martina; Keith, Stacey; Nelton, Emmalin B; Parsons, Charles S; Singleton, Jennifer; Bilello, Leslie A; Tibbles, Carrie D; Davis, Roger B; Edlow, Jonathan A; Rosen, Carlo L
Abstract: BACKGROUND: Routine follow-up head imaging in complicated mild traumatic brain injury (cmTBI) patients has not been shown to alter treatment, improve outcomes, or identify patients in need of neurosurgical intervention. We developed a follow-up head computed tomography (CT) triage algorithm for cmTBI patients to decrease the number of routine follow-up head CT scans obtained in this population. OBJECTIVE: To report our experience with protocol implications and patient outcome. METHODS: Data on all cmTBI patients presenting from July 1, 2018 to June 31, 2019, to our level 1, tertiary, academic medical center were collected prospectively and analyzed retrospectively. Descriptive analysis was performed. RESULTS: Of the 178 patients enrolled, 52 (29%) received a follow-up head CT. A total of 27 patients (15%) were scanned because of initial presentation and triaged to the group to receive a routine follow-up head CT. A total of 151 patients (85%) were triaged to the group without routine follow-up head CT scan. Protocol adherence was 89% with 17 violations. CONCLUSION: Utilizing this protocol, we were able to safely decrease the use of routine follow-up head CT scans in cmTBI patients by 71% without any missed injuries or delayed surgery. Adoption of the protocol was high among all services managing TBI patients. Graphical Abstract: